A study on loan portfolio management of Commercial Bank of Ceylon, PLC: an evaluation - Fakir, Md. Jannat (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2018.